2015
DOI: 10.1177/073989131501200103
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Formal Education of Children's Ministers in the United States: Suggestions for Professional Development, Christian Education, and Emerging Research

Abstract: There is currently no empirically supported consensus on what children's ministers need to know in order to effectively serve the children in their local congregations. To shed light on this question, this paper presents a qualitative content analysis of undergraduate children's ministry degree programs in the United States (N = 30). Findings revealed a strong emphasis on theology and general ministry preparation, with most programs drawing from the related academic disciplines of psychology and education. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Response options for each statement use a four-point Likert-type scale ranging from "Never" to "Always." In prior research, the three KCS scales demonstrated good test-retest reliability (0.88-0.95), they were sensitive to between-church differences in children's programs, and they incrementally predicted children's psychospiritual well-being (e.g., Crosby andSmith 2015, 2017;Ingersoll 2020;Smith and Crosby 2017). In the present study, Cronbach's α coefficients ranged from 0.74 to 0.80.…”
Section: Child-level Outcome Variablessupporting
confidence: 54%
“…Response options for each statement use a four-point Likert-type scale ranging from "Never" to "Always." In prior research, the three KCS scales demonstrated good test-retest reliability (0.88-0.95), they were sensitive to between-church differences in children's programs, and they incrementally predicted children's psychospiritual well-being (e.g., Crosby andSmith 2015, 2017;Ingersoll 2020;Smith and Crosby 2017). In the present study, Cronbach's α coefficients ranged from 0.74 to 0.80.…”
Section: Child-level Outcome Variablessupporting
confidence: 54%
“…Specialized collegiate degree programs in children's ministry have emerged nationally across numerous traditions (Crosby, 2015). Several universities affiliated with Churches of Christ have begun in the last few years to offer children's ministry certificates or degrees; these programs emerged after churches increasingly employed children's ministers and demonstrated the need for such education.…”
Section: The Quantitative Resultsmentioning
confidence: 99%
“…Ministry leaders either came with general training in Christian education, were heavily influenced by education, or emerged from a homegrown volunteer leader within the church. To equip an age-specialized ministry that focused primarily on children, a growing number of accredited Christian colleges and universities began “offering specialized undergraduate degrees in children’s ministry, with seasoned faculty, influential authors, and experienced practitioners responsible for deciding program requirements and developing curriculum” (Crosby, 2015, p. 27). Other organizations such as Group Publishing and the International Network of Children’s Ministries began offering curriculum, training, and resources specifically focused on those who work with children in the church (Lawson, 2004).…”
Section: A Historical Perspective Of Children’s Ministrymentioning
confidence: 99%
“…Thus, churches began specifically looking for children's pastors and directors. The challenge was that most children's ministry leaders did not have any formal training specifically in children's ministry (Crosby, 2015). Ministry leaders either came with general training in Christian education, were heavily influenced by education, or emerged from a homegrown volunteer leader within the church.…”
Section: The Growth Of a Children's Ministry Professionmentioning
confidence: 99%